(untitled) (Research, Society and Development, 2023)
The role of the Therapeutic Companion (TC) has become increasingly essential given the growth in the rate of neurodiverse children within the school environment, with the increase in the number of diagnoses such as Autism Spectrum Disorder (ASD), Attention Deficit Disorder and Hyperactivity (ADHD), Oppositional Defiant Disorder (ODD), among others. In this sense, the present study has the general objective of analyzing Brazilian scientific publications, between 2013 and 2023, on the role of the therapeutic companion (TC) within the school environment. This is a bibliographical research, the purpose of which is to provide the researcher with broad access to information, bringing together data scattered across a range of publications and contributing to a more precise theoretical-conceptual delimitation of the research object. Searches were carried out in the virtual databases Scielo, PePsic and Lilacs, using the following descriptors: therapeutic companion, school therapeutic monitoring, school inclusion and atypical children. A total of 235 articles were found and only 05 came directly from the object of study of this research. The categorization process highlighted three thematic axes: 1- School inclusion of neurodiverse children; and 2- The role of the Therapeutic Companion in the school context. It was realized that the school inclusion of atypical children is an objective to be pursued by all educational systems, creating educational environments that value diversity, respect individual differences and ensure that all children have the opportunity to develop their maximum potential, participating fully of school life and building a more inclusive and humanized future.